The Effect of Online Dictionary Use and Learning Motivation on Senior High School Students’ Reading Comprehension in English - Nanik Pujiastuti; Wawan Gunawan; Nukmatus Syahria (Rekayasa, 2025)
Reading competence is fundamental to students’ intellectual and personal development, particularly in acquiring foreign language proficiency. This study examined the effects of online dictionary use and learning motivation on English reading comprehension among secondary school students. Employing a quasi-experimental quantitative design with comparative and correlational approaches, 131 tenth-grade students from SMAN 1 Madiun participated. Data were collected using a standardized reading comprehension test and a validated 30-item motivation questionnaire. Results showed that online dictionary use and learning motivation were both positively correlated with reading comprehension (r = 0.797 and r = 0.980, respectively; p less than 0.001). Two-way ANOVA revealed significant main effects of online dictionary use (F = 106.919, p less than 0.001, η² = 0.457) and learning motivation (F = 5.943, p = 0.016, η² = 0.045), with no significant interaction effect (p = 0.133). These findings highlight the importance of integrating digital tools and motivational strategies to strengthen English reading comprehension.